Structural & Functional Prediction Of Hypothetical Proteins In Bacteriophages Against Halophilic Bacteria - An In Silico Approach - SWAPNIL G SANMUKH; WAMAN N PAUNIKAR; TARUN K GHOSH; TAPAN CHAKRABARTI (International Journal of Pharma and Bio Sciences, 2011)
The hypothetical proteins of two Halophilic phages, Halomonas phage phiHAP-1 (length 39245) and Halorubrum phage HF2 (length 77670) were studied. The structure and function predictions of hypothetical proteins were done by the use of bioinformatic web tools. In Halomonas phage phiHAP-1, function prediction for 9 and structure prediction for 3 hypothetical proteins whereas in Halorubrum phage HF2, function prediction for 32 and structure prediction for 6 hypothetical proteins were resolved. The probable function prediction was done by using Bioinformatics web tools like CDD-BLAST, INTERPROSCAN, PFAM and COGs by searching sequence databases for the presence of orthologous conserved domains in the hypothetical sequences. The tertiary structure prediction was done by using PS2 server. This study revealed some of the uncharacterized hypothetical proteins in Halophilic phages whose complete genome sequence is known and can be used for the further understanding of phage genome and its life cycle.